CHARLES DICKENS AT WORK OF “OLIVER TWIST”: HISTORY AND HEROES (Web of Teachers: Inderscience Research, 2024)
This article represents literature data about the process of creation and the presentation of Charles Dickens’ prominent novel “Oliver Twist”, written between 1837 and 1839, which reflects the suffering of the people through the fates of its characters. It discusses the history of the work and how the progression of events is portrayed. As readers know, Charles Dickens, in each of his works, depicted the social and political issues of his time as well as the joys and sorrows of the people through the lives of his characters.